(untitled) (Research, Society and Development, 2021)
One of the main methods to control the white spot of corn, chemical control with strobilurins and protective fungicides demonstrated an effect on the control of the disease, however, conditioned to the moment of its realization in phenological stages of the culture. The objective of this study was to evaluate the control and effect on the temporal progress of maize white spot with the association of the fungicides mancozeb and azoxystrobin at different timing of application, two cultivars, two planting locations and the effect on crop productivity. The experiments were conducted in the municipalities of Marechal Cândido Rondon and Sertanópolis, PR. Two susceptible hybrids were used, DKB230PRO3 and DKB290PRO3. The experimental design used was randomized blocks with 4 replications. The evaluations were carried out 10 days after each application, in addition to an evaluation at the stage of physiological maturity. The severity of the disease was evaluated by quantifying the injured leaf area in 10 plants per plot and used in the calculation of the Area Under the Disease Progress Curve, subjected to analysis of variance and the means test. The disease progress curves were adjusted to the logistic and exponential models. Yield was estimated after manual harvesting, weighing a thousand grains and yield (kg ha-1). Fungicide applications in stages V8 and V4 + V8 + VT provided control of the white spot. Applications at the V4 stage did not provide different severities from the control without application. There were no significant gains in productivity due to the application of fungicides.